Analisis Karakteristik Pedagang dan Jaringan Perdagangan Sayur Pasar Tawangmangu Kabupaten Karanganyar - Fitriyati, Aprilia Dwi, Drs. M. Musiyam, M.TP, Dra. Umrotun, M.Si (2016)
This research aims for analyze the characteristics of market traders in Tawangmangu, and analyze Network Trade Vegetable Market Tawangmangu. The methods that used in this research is a survey to research area using a purposive sampling method, whereas in research using the technique of simple random sampling with fetch sampling as much as 45% of the total number of vegetable traders or 69 of 31 respondents. On the results obtained that the Characteristics of vegetable traders in the market are traders in Tawangmangu Tawangmangu Market the majority of women (90,32%), age of vegetable Market Traders Tawangmangu most productive age (96.78%), the level of education the last Vegetable Market Traders Tawangmangu average graduates of elementary school (51,63%), Old Vegetable Market Traders trading venture Tawangmangu between 11-20 years (45,18%), mostly traders originating from Tawangmangu Sub-district (64,51%), the number of dependents family owned trader between 2-5 people (87,09%) Merchant Capital, between Rp. 1,000,000-Rp. 10,000,000 (54,83%). A network of trade that occurs from the market to other Markets to area Tawangmangu Tawangmangu supplying vegetables to the Solo, Sragen, Sukoharjo and who became the intermediary is the collecting of merchant, network trade that occur from other regions to markets Tawangmangu is coming from Wonosobo, Boyolali, Magetan, and there are also derived from East Java that is derived from the Kediri, Banyuwangi, and Magetan. With the partnership that owned the merchant of merchant ventures, the larger then the merchants more to sell vegetable supplies to the relaso in the other.